The Face of the General Elections Commission in The Case of the Code of Conduct 2018-2020 - Paisal Akbar; Mohammad Taufik; Bambang Irawan; Sonny Sudiar (Mengeja Indonesia Publisher, 2021)
The course of the implementation of the General Election can never be separated from all kinds of ethical and criminal matters that always color in the course of the electoral stage in Indonesia. Several cases of violations of the ethics code and corruption committed by the Commissioners and Secretariat of the KPU at all levels resulted in sanctions imposed by the DKPP against the KPU. Therefore, the results of this study will look at the case of the KPU code of ethics in the DKPP decision for the 2018 to 2020 period, as well as the impact of this decision on election organizers at the KPU. This study using a qualitative descriptive research design. The data used in this study were obtained from literature studies in the form of documents of the results of the verdicts that have been issued by the DKPP obtained through the official portal website of the DKPP, with a period from 2018 to 2020. The document of the decision of the DKPP ethics case was then carefully processed by the author using the application of qualitative data processing Nvivo 12 Plus. The data processing results found that enrichment of the electoral code of conduct by-election organizers in the KPU is still felt less. All parties should highly praise preventive efforts to violate the code of conduct.